Female and royal humanity? One African woman's meditation on Psalm 8 - Masenya, Madipoane (Old Testament essays, 2014)
In 2008, the legal case of the now Hosi (chief) N'wamitwa II made headlines in South Africa. Although a legitimate heir to her father's throne, N'wamitwa's gender posed the main hindrance to her assuming the royal position. The preceding scenario reveals that even fourteen years into the non-racist, non-sexist post-apartheid South Africa, there was still opposition among many Africans to women leading communities as traditional leaders; that is, a belief that women lacked the capacity to rule. Dare one say this remains so even today? A rereading of Ps 8 reveals the equality and royalty of all human beings irrespective of their gender, among others. The main question the present article seeks to investigate concerns what it means to be a human being both in an African-South African context as well as in the meditation presented by Ps 8. In particular, if Ps 8 is re-read from the perspective of a context in which female humanity (read: women) must at times go through a legal process in order to rule, one in which female humanity seems to be contested, which insights might emerge from such a reading?